Sistem Pemantauan dan Kontrol Energi Listrik Menggunakan Platform Node-RED, Influxdb dan Grafana melalui Jaringan WiFi dan Lora - Arifianto, Mada Jimmy Fonda; Prasetyani, Lin (Universitas Halu Oleo, 2022)
Electrical energy monitoring for home and industrial equipment plays important role to prepare the concept of green energy in the future. Usually, only one or a few energy meters are provided in each building for monitoring the energy use of the entire installation. Usually, only one or a few energy meters are provided in each building for monitoring the energy use of the entire installation. Topic of this research is developing an energy measuring instrument that is applied to every electrical equipment. Knowing the information of energy usage of each equipment in real-time is the first step in saving electricity.Â This help for decisions making in term of efficient utilization, for example managing the schedule of production system and preventive maintenance. The energy monitoring and controlling system proposed in this paper includes hardware development using microcontroller ESP32, LoRa module and energy sensor PZEM-004T.Â In addition, software development to support the system includes Node-RED as dashboard and back-end development, InfluxDB as database management and Grafana as data visualization. The prototype has been successfully made and has features according to the research objective, which is to display the electrical quantity of each tool individually and monitor it for a certain period.